Analisis Perilaku Hidup Bersih dan Sehat (PHBS) Sebagai Upaya Pencegahan Covid-19 di SD Negeri 2 Pengkol Jepara - Alda Refayanti Agustina; Ferina Agustini; Asep Ardiyanto (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
Analysis Of Clean And Healthy Living Behavior (PHBS) As An Effort To Prevent Covid-19 In 2 Pengkol Jepara Public Elementary Schools. This study aims to implement clean and healthy living behavior (PHBS) as an effort to prevent COVID-19. This research is qualitative research using a descriptive approach. The subjects used were all grade I-VI students of SD Negeri 2 Pengkol Jepara. Sources of data obtained through observation, interviews, questionnaires and documentation. Checking the validity of the data in this study using triangulation techniques. The results showed that in grades I - VI at SD Negeri 2 Pengkol Jepara, they had applied it well, although there were some children who still could not apply it well. In implementing clean and healthy living behavior, teachers have taught the implementation of PHBS well as well as the parents of students. In contrast to students, there are some students who have not been able to apply it well with the students' own awareness. Based on the results of this study, the advice that can be conveyed is to familiarize students with implementing clean and healthy living behaviors, students can avoid disease and can prevent the virus that we are facing, namely covid-19.